Identification and Speciation of Aspergillus in Clinical and Environmental Samples using Culture-Based Methods: A Laboratory-based Study in Hyderabad - Shaik Begum Meherunnisa; Mohd Ubaidullah Ansari; Mohammed Yasser Arafath K M; Juveria Sultana (Perspectives In Medical Research)
Background: Aspergillosis is increasingly recognized as a serious opportunistic infection, particularly among immunocompromised patients. Accurate species-level identification of Aspergillus is critical for selecting appropriate antifungal therapy and implementing effective infection control measures. This study aimed to identify and characterize Aspergillus species isolated from both clinical specimens and indoor air samples at a tertiary care hospital in Hyderabad, Telangana, India. Methods: Over a one-year period, a total of 709 specimens—including nasal mucosa swabs, tissue biopsies (lung, FESS), blood samples, nail clippings, and passive indoor air seƩle plates—were processed in the microbiology laboratory. Direct microscopic examination was performed using KOH mount, periodic acid–Schiff stain, and calcofluor white stain. Specimens showing filamentous fungi were cultured on Sabouraud dextrose agar. potato dextrose agar, corn meal agar, Czapek medium, and malt extract agar, and incubated at 25–30 ◦C for 7–10 days. Species identification was based on detailed assessment of colony morphology and microscopic features (conidiophore structure, vesicle shape, phialide arrangement, and conidial ornamentation), following CLSI guidelines. Results: Out of 709 specimens, Aspergillus species were isolated from 239 samples (33.7%). Thirteen species were identified, with A. flavus being the most common (33.4%), followed by A. niger (26.7%), A. fumigatus(19.2%), A. nidulans(4.6%), A. glaucus (3.3%), A. terreus (2.9%), A. versicolor (2.1%), A. calidoustus (1.7%), A. glabrata (1.7%), A. parasiticus (1.2%), A. clavatus (1.3%), A. ochraceus (0.8%), and A. tanneri (0.8%). A. flavus predominated among both clinical and environmental isolates. Conclusion: Conventional morphological methods combined with the use of multiple culture media proved effective for species-level identification of Aspergillus. Routine surveillance of Aspergillus species in both clinical and environmental samples can guide targeted antifungal therapy and support proactive infection control in healthcare environments. KEYWORDS: Aspergillus, Speciation, Differential Media, Clinical specimens, Environmental surveillance